EFFECT OF BLENDED TRIPLE SUPERPHOSPHATE WITH UREA ON N, P CONCENTRATIONS IN PLANT AND GROWTH OF BROAD BEAN IN A GYPSIFEROUS SOIL - Farhan, M. J.; Muhawish, N. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A field experiment was conducted on a gypsiferous sandy clay loam soil to examine the effects of blending Triple superphosphate (TSP) with urea on N, P concentrations in plant and growth parameters of broad bean. The experiment was a factorial randomized complete block design (RCBD) with three replicates. The first factor was type of application as briquettes which include T1 (one layer of TSP between two layers of urea) and T2 (one layer of urea between two layers of TSP), the second factor was application depth (5 and 10 cm D1 and D2), and the third factor was application rate (1.0, 1.25, and 1.50 as much as N and P fertilizer recommended for broad bean, R1, R2 and R3). Broad bean was planted and the following growth parameters were taken: plant height, no. of leaves, plant dry weight, chlorophyll content, leaf area, N and P concentration in plant. Results showed that the following treatments: T1 of blending (briquette no. 1), D1 and R2 were significantly superior over other treatments in all growth parameters and N, P concentration in plant. The triple interaction treatment T1D1R2 was significantly superior over other treatments with values reached 60.99 cm, 442.7 leave plant-1, 20.32 cm2, 63.87 Spad, 5.59 g plant-1, 5.55 %, and 0.27 %, respectively for plant height, no. of leaves plant-1, leaf area, chlorophyll content, plant dry matter, N and P conc. in plant.